Role play as an active technique to improve speaking - Villamar Gavilanes, Miriam Jacqueline; Suárez Galarza, Daniela Mahely (Machala: Universidad Técnica de Machala, 2023)
Currently, the English Language is a fundamental tool for communication around the world and in the Ecuadorian educational system, opportunities for students to practice a second language within the classroom are often very limited. This limitation is because of the lack of class hours, hence teachers must provide their students with options to improve their oral skills. For this reason, the current study aims to develop a system of activities using the active teaching-learning role-play technique to enhance English oral skills. This research was conducted within a quantitative paradigm, employing an experimental design with a sample of 30 students enrolled in the sixth semester A of Pedagogy in National and Foreign Language for the 2023-1 period. During the investigation, it was considered to use theoretical methods such as historical-logical, analytical-synthetic, hypothetical-deductive, and systematic methods, as well as empiric methods such as observation, experimentation, measurement, and pedagogical testing. Finally, the results of the hypothesis verification manifest that when applying a system of activities, there is indeed evident progress in the student’s oral skills.
Actualmente, el idioma inglés es una herramienta fundamental para comunicarse en el mundo y a menudo, en el sistema educativo ecuatoriano, las oportunidades de los estudiantes de practicar un segundo idioma dentro del aula, son muy limitadas debido a la escasa cantidad de horas de clase, por lo tanto los docentes deben brindar opciones a sus estudiantes para mejorar su competencia oral. Es por eso, que el estudio que se presenta tuvo como objetivo elaborar un sistema de actividades utilizando la técnica activa de enseñanza - aprendizaje role play para el mejoramiento de las habilidades orales del idioma inglés. Se desarrolló desde una perspectiva cuantitativa de tipo experimental en un nivel pre-experimental con una población de 30 estudiantes del sexto semestre paralelo A de Pedagogía de los Idiomas Nacionales Extranjeros periodo 2023-1. Durante la investigación se consideró el uso de métodos de nivel teórico como el método histórico-lógico, analítico-sintético, e hipotético-deductivo y sistémico, como también métodos de nivel empírico entre los cuales se incluyen la observación, la experimentación, la medición y la prueba pedagógica. Finalmente, los resultados de la verificación de la hipótesis evidencian que al aplicar el sistema de actividades, efectivamente existe un progreso notorio en la habilidad oral de los estudiantes.
Keywords: EXPRESION ORAL; ROLE PLAY; IDIOMA INGLES; FLUENCY